The Regional Innovation System and Smart Specialisation in the “energy region” Lusatia - Caron Pomp (List Forum für Wirtschafts- und Finanzpolitik, 2023)
Lusatia, a~rural-peripheral region in Eastern Germany, currently faces structural change due to the planned phase-out of lignite mining. Against the backdrop of the EU Smart Specialisation (S2) strategy, structural change funds need to be invested where it can strengthen Lusatia's Regional Innovation System (RIS). With Lusatia's history, energy seems a~promising topic S2. However, it is questionable if there is a~critical mass of actors and research for energy topics in the region that could enable regional competitiveness. This paper addresses this issue by analysing the current state of Lusatia's RIS and the potentials for S2. I~use empirical data from statistical offices and the "Förderkatalog" as well as data on new research projects and institutes for my analysis. The gathered data suggest that the region's RIS is rather thin. While the proclaimed image of an "energy region" is not reflected in the data yet, this may change due to the structural change program and the strategic orientation of the region. S2 may be successful if the new institutes and research projects enable the attraction of skilled workers and firms and at the same time manage to increase the absorption capacity of existing firms in the region. Building a~critical mass for cooperation and innovation is achievable, at least in the larger cities such as Cottbus. Monitoring and evaluation of the impacts of the invested funds will be crucial.
Keywords: 330; Regional Innovation Systems; Smart Specialisation; Periphery; Energy; Regionale Innovationssysteme; Intelligente Spezialisierung; Peripherie; Energie